2015
DOI: 10.1016/j.supflu.2014.12.023
|View full text |Cite
|
Sign up to set email alerts
|

A trade-off between maxima in efficiency and specific work output of super- and trans-critical CO2 Brayton cycles

Abstract: a b s t r a c tSeveral operational aspects for thermal power plants in general are non-intuitive and involve simultaneous optimization of a number of operational parameters. In the case of solar operated power plants, it is even more difficult due to varying heat source temperatures induced by variability in insolation levels. This paper introduces a quantitative methodology for load regulation of a CO 2 based Brayton cycle power plant using the 'thermal efficiency and specific work output' coordinate system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…To realize a meaningful throughput Srinivasan et al [28] recommend that a minimum uptake efficiency of 40% must be targeted. Because of this limitation thermal compression ratio diminishes further and is found to remain fairly constant at about 2.3 [23] which is again comparable to the optimal expansion ratio for a sub-critical conventional Brayton cycle. The thermal efficiency of adsorption compression Brayton cycle against specific work per unit mass of activated carbon required is shown in Fig.…”
Section: Co2 Subcritical Brayton Cycle With Thermal Compressionmentioning
confidence: 65%
See 3 more Smart Citations
“…To realize a meaningful throughput Srinivasan et al [28] recommend that a minimum uptake efficiency of 40% must be targeted. Because of this limitation thermal compression ratio diminishes further and is found to remain fairly constant at about 2.3 [23] which is again comparable to the optimal expansion ratio for a sub-critical conventional Brayton cycle. The thermal efficiency of adsorption compression Brayton cycle against specific work per unit mass of activated carbon required is shown in Fig.…”
Section: Co2 Subcritical Brayton Cycle With Thermal Compressionmentioning
confidence: 65%
“…This is also one of the conclusions of Cayer et al [39] in a context of a free heat source like industrial waste gases where the focus should be on maximising the specific net output rather than the thermal efficiency. This aspect has been investigated in greater detail by Garg et al [23]. For the transcritical Rankine cycle the efficiency vs specific net work output plane is shown in Fig.…”
Section: Co 2 As a Rankine Cycle Fluidmentioning
confidence: 97%
See 2 more Smart Citations
“…Wang et al [27] conducted multi objective optimisation of geothermal power plant operating in transcritical CO 2 cycle and utilizing LNG as heat sink. Analysis conducted by Garg et al [28] revealed that though transcritical CO 2 cycle provided more flexibility under part load performance for non solar application, supercritical CO 2 cycle was a better option for the concentrated solar power system.…”
Section: Introductionmentioning
confidence: 99%